Analisa Visualisasi Data Covid – 19 Di Indonesia Menggunakan Tableau Big Data - Pangestu, Prayoga; Hartama, Dedy; Suhendro, Dedi; Damanik, Abdi Rahim; Oktaviani, Selli (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study explains the benefits of data analysis by visualization of Big data inoptimizing cases of the spread of COVID-19 in Indonesia. The data used is the COVID-19 Indonesia time series data from the Kaggle website. In this study, the author used tableau tools to analyze data based on worksheets of covid-19 distribution maps, COVID-19 statistics, details of active cases per province, death cases per province, active cases, death cases, confirmed cases and produced a dashboard of COVID-19 data. The results of the analysis obtained using visualizations in the form of graphs are very fast and optimize data processing so that they can find out which provinces are affected by active cases and deaths of COVID-19 from the highest to the lowest in Indonesia and can be used in decision and policy making for the Indonesian government.